THE EFFECT OF REPEATED READING STRATEGY ON READING FLUENCY: THE CASE OF STUDENTS WITH READING DIFFICULTIES AT SMP AL-IKHLAS KEDIRI - Imam Suhaimi (LPPM Universitas Kahuripan Kediri, 2018)
Reading can be said a complex endeavor that is made up of multiple components, all of which must be orchestrated and executed by the reader with the goal of making meaning from the text. Reading effectively requires the readers to make accurate sense of the text by making inferences based on connections beyond and within the current text. This study investigated the effects of a reading strategy, repeated readings on reading fluency. Three students as members of two classrooms in one junior high school participated in this 2 weeks study. The research employed a quantitative means by using pre-experimental Design. A pre – Post - test design was used. The results of this study indicate that repeated reading strategy is found to be overall effective on reading speed and reading accuracy. This study has some recommendations for teaching instructions and research. For example, teachers can use it as an instructional approach for improving the reading fluency not only for those with reading difficulties, but for all students. As for research, future studies should consider including a larger number of students who experience reading difficulties. Key words: Repeated reading, reading fluency, and reading difficulties